Exploring public participation process and its differing degrees in influencing risk perception within the petrochemical industry: a scoping review - Gheitasi, Mahdi; Serrano Giné, David; Pérez-Albert, Yolanda (Frontiers in Environmental Science, 2023)
To evaluate perceived risk, it is necessary to understand both the type of risk and the residents' perceptions. With the rise of information on technology and digital platforms, new avenues have emerged for examining citizens' risk perception in participatory settings. However, the lack of theoretical and methodological approaches in this area calls for further research. The objective of this article is to fill the existing research gap by conducting a scoping review of published literature that examines risk perception related to the petrochemical industry, specifically focusing on digital platforms and the utilization of participatory processes in assessing risk perception within this industry context. The review analyzes the types of questions and responses encountered during participatory processes. The authors selected and studied 10 papers in-depth after applying specific selection criteria. They identified two types of risks - natural and technological - associated with the petrochemical industry, and two types of questions: general questions such as demographics, education, and employment, and specific questions such as risk perception, trust in government and company information, type of risk, or proximity to polluted areas. The paper identifies two question types in participatory processes: general and specific. It emphasizes that the most frequent participation level is consultation, involving seeking public feedback for decision-making. Risk perception is a common topic in participatory processes, highlighting the importance of understanding and addressing public concerns about activities risks. Understanding risk and questions raised during participation is crucial to studying risk perception. This knowledge can improve policies, identify risk mitigation solutions, and identify relevant questions to aid in logical answers.